When arm's length is too far. Relationship banking over the business cycle - Thorsten Beck; Hans Degryse; Ralph De Haas; Neeltje van Horen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
Using a novel way to identify relationship and transaction banks, we study how banks' lending techniques affect funding to SMEs over the business cycle. For 21 countries we link the lending techniques that banks use in the direct vicinity of firms to these firms' credit constraints at two contrasting points of the business cycle. We show that relationship lending alleviates credit constraints during a cyclical downturn but not during a boom period. The positive impact of relationship lending in an economic downturn is strongest for smaller and more opaque firms and in regions where the downturn is more severe.
URN:NBN:fi:bof-201411063129
Keywords: F36; G21; L26; O12; O16; 330